Levels, solid-phase fractions and sources of heavy metals at site received industrial effluents: a case study. Issue 1 (1st January 2017) - Usman, Adel R. A.; Almutairi, Abdulelah Abdullah; Elmaghraby, Salem; Al-Farraj, Abdullah S.
Abstract: Heavy metals in the site received industrial effluents were investigated to assess the pollution levels, distribution of metal among solid-phase fractions and possible metal sources. The soil samples at different depths of 0–5, 5–25 and 25–50 cm were collected and analyzed for Fe, Mn, Cd, Zn, Cu, Ni and Pb. Among all metals, Cd content was not detected in all soil samples. The average contents of Pb and Zn are higher than the corresponding values of common range in earth crust. Meanwhile, the maximum contents of Cu and Zn are higher than those of Dutch optimum value but lower that the Dutch protection act target value. The maximum contents of Cu, Pb and Zn are higher than the average shale value. The most investigated heavy metals are mostly found in the potentially labile pool (>50.0%) including metal bound to carbonate, Fe/Mn oxides, or organically fractions. Enrichment factor (EF) in combination with multivariate analysis including principal component analysis (PCA) and hierarchical cluster analysis (HCA) suggest that Mn and Ni associated with Fe in the soil samples were primarily originated from lithogenic sources. Pb was largely derived only from anthropogenic source, while Cu and Zn in the soil samples were controlled by the mixed natural and anthropogenic sources. These results suggest that discharging the industrial effluents into dumping site increased pollution level of Pb, Zn and Cu as well as enhanced their potentially labile pool that may be responsible for occurring potential toxic impacts on environmental quality.